Diagnostic fibreoptic bronchoscopy in the immunocompromised host with pulmonary infiltrates. Issue 5 (October 1977) - Matthay, R A; Farmer, W C; Odero, D
Abstract : Nineteen immunocompromised patients with pulmonary infiltrates underwent diagnostic fibreoptic bronchoscopy with transbronchial forceps and brush biopsy. A specific diagnosis was obtained in 21/25 procedures (10/11 focal lesions and 11/14 diffuse legions). The most common diagnosis was infection, and organisms isolated included bacteria, fungi, Pneumocystis carinii, and herpes simplex. A pneumothroax requiring tube drainage occurred in two cases and mild lung parenchymal bleeding was noted in two others. It is concluded that fibreoptic bronchoscopy with forceps and brush biopsy can be performed safely with an excellent diagnostic yield in immunocompromised hosts with lung lesions. Supplemental oxygen should be administered during fibreoptic procedures in these patients and platelet transfusions should be given when thrombocytopenia is present.